Where we were . . . where we are heading: One multiplicative journey - Hurst, Chris; Hurrell, D. (Australian Asssociation of Mathematics Teachers, 2017)
A journey into multiplicative thinking by three teachers in a primary school is reported. A description of how the teachers learned to identify gaps in student knowledge is described along with how the teachers assisted students to connect multiplicative ideas in ways that make sense.